2021
DOI: 10.1175/bams-d-20-0186.1
|View full text |Cite
|
Sign up to set email alerts
|

From Random Forests to Flood Forecasts: A Research to Operations Success Story

Abstract: Excessive rainfall is difficult to forecast, and there is a need for tools to aid Weather Prediction Center (WPC) forecasters when generating Excessive Rainfall Outlooks (EROs), which are issued for the contiguous United States at lead times of 1–3 days. To address this need, a probabilistic forecast system for excessive rainfall, known as the Colorado State University-Machine Learning Probabilities (CSU-MLP) system, was developed based on ensemble reforecasts, precipitation observations, and machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Artificial intelligence (AI) and machine learning (ML) have recently exploded in popularity for a wide variety of environmental science applications (e.g., McGovern et al, 2019; Reichstein et al, 2019; Gagne et al, 2020; Gensini et al, 2021; Hill and Schumacher, 2021; Lagerquist et al, 2021; Schumacher et al, 2021). Like other fields, environmental scientists are seeking to use AI/ML to build a linkage from raw data, such as satellite imagery and climate models, to actionable decisions.…”
Section: Motivationmentioning
confidence: 99%
“…Artificial intelligence (AI) and machine learning (ML) have recently exploded in popularity for a wide variety of environmental science applications (e.g., McGovern et al, 2019; Reichstein et al, 2019; Gagne et al, 2020; Gensini et al, 2021; Hill and Schumacher, 2021; Lagerquist et al, 2021; Schumacher et al, 2021). Like other fields, environmental scientists are seeking to use AI/ML to build a linkage from raw data, such as satellite imagery and climate models, to actionable decisions.…”
Section: Motivationmentioning
confidence: 99%
“…[9]. The model has successfully emerged as an alternative forecasting method in some fields and obtained excellent results, such as daily and monthly rainfall prediction [10,11], flood prediction [12], and monthly EP indices prediction [13]. Herman et al [14] explored the RF algorithm to forecast short-term EP in America, and found that the RF-based prediction was quite reliable.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of this method can also be used, for example, to predict ground characteristics such as soil temperature or greenhouse water content (Tsai et al, 2020). From a purely meteorological perspective, it can be used to forecast complex processes and influential phenomena such as flood forecasting (Schumacher et al, 2021) or extensive rainfall (Hill and Schumacher, 2021). However, both of the aforementioned works have also applied this method to NWP outputs.…”
Section: Introductionmentioning
confidence: 99%